2015
DOI: 10.1039/c5fo00260e
|View full text |Cite
|
Sign up to set email alerts
|

Targeted anti-colon cancer activities of a millet bran-derived peroxidase were mediated by elevated ROS generation

Abstract: Foxtail millet (Setaria italica) is the sixth most important cereal in the world. In particular, the millet-derived active components play important roles in disease prevention. In this study, we found that a peroxidase from foxtail millet bran, named FMBP, displayed profound inhibitory effects on the growth of human colon cancer cells, but not on that of the normal colon epithelial cells. Mechanistic investigations suggested that the selective anti-cancer effects of FMBP were mainly achieved by inducing more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Immunohistochemistry was implemented as previously described [ 46 ]. The paraffin sections were de-waxed in xylene and dehydrated in concentration gradient ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was implemented as previously described [ 46 ]. The paraffin sections were de-waxed in xylene and dehydrated in concentration gradient ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…ROS are important intracellular mediators playing roles in maintaining normal cellular functions and causing cell injuries and cell death [18]. Many anti-cancer agents cause cell damage by generating excessive ROS [19]. Previous investigations suggested the role of ROS as one of the initiators of ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Whole grains have an outer bran coat, a starchy endosperm, and a germ. Concerning the medicinal values of grains, previous studies have demonstrated that active ingredients such as polyphenols in sorghum bran [ 4 ], protein and peroxidase in millet bran [ 5 ], soluble phenolic content [ 6 ] and oil [ 7 ] of rice bran, and fermented rice bran-containing diet [ 8 ], could have suppressive effects on colitis and colon cancer cell growth. The bioactive phytochemicals present in rice bran such as ferulic acid, tricin, β-sitosterol, g-oryzanol, tocotrienols/tocopherols, phytic acid are regarded to possess chemo-preventive potential [ 9 ].…”
Section: Introductionmentioning
confidence: 99%